Endovascular treatment of Budd–Chiari syndrome: Single center experience. Issue 1 (January 2017) - Rathod, Krantikumar; Deshmukh, Hemant; Shukla, Akash; Popat, Bhavesh; Pandey, Ankur; Gupte, Amit; Gupta, Deepak Kumar; Bhatia, Shobna J
Abstract: Background and Aim: Percutaneous radiologic interventions are increasingly being used in management of Budd–Chiari syndrome (BCS). Minimal invasive approach has resulted in excellent long‐term outcomes. We evaluated the treatment efficacy and safety of radiological intervention in patients with BCS. Methods: Between January 2008 and June 2014, 190 patients with BCS underwent endovascular procedures (hepatic vein, collateral vein or inferior vena cava [IVC] plasty with or without stenting, or transjugular intrahepatic portosystemic shunting [TIPSS]). Clinical features, biochemical profile, and stent patency were monitored pre‐procedure and post‐procedure, and for a median duration of 42 (12–88) months. Results: Of 190 patients (mean [SD] age = 26.9 [11.5] years; 102 men), imaging revealed hepatic vein obstruction in 147 patients, IVC obstruction in 40 patients, and concomitant hepatic vein and IVC obstruction in three patients. At presentation, the radiological interventions included hepatic vein plasty/stenting in 38 patients, collateral vein stenting in three patients, IVC plasty/stenting in 40 patients, both IVC and hepatic vein stenting in three patients, and TIPSS in 106 patients. Response was seen in 153 patients (80.5%). Repeat interventions were required in 19 patients (10.0%). Complications were noted in nine patients (4.7%). Conclusion: Our study demonstrates that venous recanalization and TIPSS for BCS are safe and efficacious.